2004
DOI: 10.1038/ni1053
|View full text |Cite
|
Sign up to set email alerts
|

A cis element in the recombination activating gene locus regulates gene expression by counteracting a distant silencer

Abstract: We have identified a silencer and an antisilencing element that interact at a distance of 85 kilobases to regulate expression of the recombination activating genes Rag1 and Rag2 in thymocytes. Transgenic experiments showed that Rag promoter-proximal cis elements directed tissue-specific expression and that a Runx-dependent intergenic silencer suppressed expression in developing T cells. Deletion of the antisilencing element from the genomic Rag locus unmasked the intergenic silencer and abrogated Rag expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 49 publications
6
68
0
Order By: Relevance
“…IL-6 may activate factors that trigger the transcription of RAG genes (47), or it may give rise to factors that push cis elements into counteracting the silencer that normally represses RAG gene transcription (48). More likely, IL-6 may increase the expression level of BR-3, as was recently demonstrated in cytokine-stimulated B cells (49), or it may help to reduce receptor numbers occupied by soluble BAFF to favor transmembrane BAFF engagement (50).…”
Section: Discussionmentioning
confidence: 95%
“…IL-6 may activate factors that trigger the transcription of RAG genes (47), or it may give rise to factors that push cis elements into counteracting the silencer that normally represses RAG gene transcription (48). More likely, IL-6 may increase the expression level of BR-3, as was recently demonstrated in cytokine-stimulated B cells (49), or it may help to reduce receptor numbers occupied by soluble BAFF to favor transmembrane BAFF engagement (50).…”
Section: Discussionmentioning
confidence: 95%
“…Three distal elements involved in regulation of RAG genes were also identified and found to be located within 22 kbp of the 5 0 end of RAG2 [15,16]. In addition, a silencer located in the intergenic region between RAG1 and RAG2 and an anti-silencer located between 71 and 86 kbp 5 0 of RAG2 were recently described [17].…”
Section: Introductionmentioning
confidence: 99%
“…It is juxtaposed to the 3 0 end of RAG1 andin the mouse and other species relatively well represented in databases, like human and chimpanzee -has its 5 0 untranslated region in the intron of RAG2. In the From the left to the right they are: anti-silencer [17], Erag [16], D3 [15], an element located 2 kbp 5 0 of RAG2 [15] and a silencer [17]. The positions of the primers used in this study are indicated by dotted horizontal arrows.…”
Section: Identification Of Nwc a Third Gene Within The Rag Locusmentioning
confidence: 99%
“…DP thymocytes that have successfully generated an ␣␤ TCR express higher TCR␤ chain levels and are referred to as TCR␤ int DP thymocytes. TCR␤ int DP thymocytes continue to undergo V␣ to J␣ rearrangements until recombinase activating gene (RAG) -1 and -2 expression is terminated by the signals of positive selection (12)(13)(14)(15)(16)(17)(18). Thus, a productive VJ␣ rearrangement that does not encode a TCR␣ chain capable of positive selection could be excised and replaced with a new VJ␣ ( Fig.…”
Section: V(d)j Recombination ͉ Gene Rearrangement ͉ T Cell Repertoirementioning
confidence: 99%